The Impact of a Preretirement Program - Bond, Sheryl L.; Bond, Jr, John B. (Canadian Journal of Counselling and Psychotherapy, 2012)
A ten week preretirement program was provided to 14 employees of a medium sized corporation, and seven spouses. After the participants identified topics of concern, an interactional format was used to present the information. Atttitudes toward retirementwere determined at the beginning of the program; at the end of the course, and six months later, both attitudes and degree of goal attainment were assessed. Attitudes toward retirement consistently improved, both during the program (P<.01) and six months following completion of the program (p<.01). No significant decreases in goal attainment were reported during the six months for goals existing prior to the course, or developed during the course.